EKSPLORASI NILAI KEPEDULIAN SOSIAL SISWA MELALUI PENDIDIKAN KEWARGANEGARAAN BERBASIS ISU LINGKUNGAN - Aulia Pratama Putri; Niscaya Amanda Agustin; Adinda Putri Sopiah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Civic Education (PKN) is an essential foundation in forming individuals with noblecharacter and responsibility as citizens. Samsuri (2011: 20) emphasizes that CivicEducation, along with character development, in building public morality andpersonality, but also instilling ethical values so that they grow into quality citizens.One effective approach to fostering social awareness and responsibility of theyounger generation is through exploring social concerns by integrating CivicEducation based on environmental issues. This approach is relevant because italigns civic values ​​with contemporary environmental challenges, supporting therealization of environmental sustainability. Schools, as formal educationalinstitutions, play a crucial role in shaping students' character.